“They don't care about people; they only care about the money”: the effects of border enforcement, commodification and migration industries on the mobility of migrants in transit through Mexico - Willers, Susanne (Frontiers in Sociology, 2023)
How does border enforcement affect the mobility of migrants and refugees in countries of transit? What impact does it have on migrants' bodily experiences of mobility and their reliance on actors of the migration industry? While the externalization of borders affects undocumented people by increasing their vulnerability to violence during transit, the impact of the migration regime on the social construction of inequalities in every-day interactions and its relationship to the capacity for mobility has not been studied in depth. This article intends to bridge this gap: based on ethnographic fieldwork I conducted between 2013 and 2019, this article analyzes the relation between immigration enforcement and the mobility strategies of migrants and refugees, particularly women. It focuses on the intertwining of border enforcement and violence and their impact on people's bodily mobility experiences in transit through Mexico along intersecting lines of inequality such as race, class, gender and nationality. First, I analyze how border enforcement contributes to internal bordering, thereby increasing the vulnerability and dependence of migrants on brokers for mobility; second, it looks at the bodily experiences of women in transit and the ways in which internal bordering shapes gendered power hierarchies among actors in the field of mobility. The analysis shows how women negotiate mobility and bodily integrity in social interactions with different actors and how they face constraints resulting from the gendered hierarchies to mobility on routes of transit. Furthermore, it demonstrates how women's bodies have become a privileged site for the construction of a 'body politic' exploitable by others, since border enforcement has contributed to weakening the possibilities of negotiating mobility and bodily integrity in transit.